Absenteísmo-doença entre profissionais da enfermagem atuantes na urgência e emergência: estudo transversal em hospital público de Belo Horizonte - MG - Ronaldo Machado Silva (2018)
Absenteeism is understood as the employee's lack of work, and in the nursing team is directly linked to working conditions, reflecting the quality of care provided and the health of these workers. The objective of this study was to estimate the prevalence of absenteeism-disease among Nursing professionals working in the emergency and emergency of a public hospital, as well as to investigate the factors associated with absenteeism-disease. This is a descriptive and analytical research, contemporary documentary, with a quantitative and transversal approach. The population was the nursing team of the emergency/emergency sector (Emergency Relief), approached through a census, and composed of 294 professionals, of which 237 were at the elementary / middle level and 57 at the higher level. The data were collected through the functional charts of the first-aid workers and analyzed using Microsoft® Excel and IBM SPSS-StatisticalPackage for the Social Science - version 12 and treated by means of descriptive statistics, statistical tests (Chi-square of Pearson and non-parametric Mann-Whitney test) and logistic regression models. Results were obtained: 69% (IC = 95% [63%, 74%]) of the study population had at least one medical license application in 2016, and the following groups had a higher chance of absenteeism, according to model of logistic regression used: nursing technicians, younger individuals in the age group 21 to 30 years, who have children, those who receive higher remuneration, statutory employment relationship and those who work in the ready subsector. The most prevalent groups of diseases according to ICD 10 were diseases of the respiratory system, diseases of the musculoskeletal system and connective tissue, some infectious and parasitic diseases, and factors influencing health status and contact with health services, When analyzing the index of absenteeism for the nursing team in the emergency and emergency service in question, it was verified that it was 8.0, being considered in the literature a high index. The months that generated the greatest number of days of leave were July and September and, in relation to the days of the weeks that had more leaves, were Thursdays and Fridays. The results of this research may contribute to the discussion and reflection about the object of study, aiming at reducing the negative impacts of absenteeism that affect the managers, workers and users of health services. It is concluded that the analysis of absenteeism can contribute to provide information on the health status of nursing workers, as well as be an indicator for managers regarding professional satisfaction and identify working conditions that lead to it.Key Words: Absenteeism. Nursing. Urgency and Emergency. Emergency Medical Services.